2018
DOI: 10.1111/add.14503
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with ecological momentary assessment protocols in substance users: a meta‐analysis

Abstract: Background and Aims While there are considerable benefits to Ecological Momentary Assessment (EMA), poor compliance with assessment protocols has been identified as a limitation, particularly in substance users. Our aim was to identify the pooled compliance rate of EMA studies in substance users and examine variables that may influence compliance with EMA protocols, such as the length and frequency of assessments. Design A meta‐analysis and meta‐regression of all possible studies (randomized controlled trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
252
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 245 publications
(300 citation statements)
references
References 68 publications
39
252
9
Order By: Relevance
“…The current BURDEN, COMPLIANCE & CARELESS RESPONDING IN ESM DATA results suggest that these variations in questionnaire lengths can have a measurable impact on burden, data quality, and quantity. Most previous analyses have failed to find an association between questionnaire length and compliance (Jones et al, 2018;Ono et al, 2019;Soyster et al, 2019;Vachon et al, 2019), however some of these findings were limited by the availability of information on full questionnaire lengths. Moreover, while these analyses did control for the effects of some other design characteristics of the included studies, more subtle aspects (such as the detail of instructions, which might be adapted to the protocol intensity in individual studies) were not included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current BURDEN, COMPLIANCE & CARELESS RESPONDING IN ESM DATA results suggest that these variations in questionnaire lengths can have a measurable impact on burden, data quality, and quantity. Most previous analyses have failed to find an association between questionnaire length and compliance (Jones et al, 2018;Ono et al, 2019;Soyster et al, 2019;Vachon et al, 2019), however some of these findings were limited by the availability of information on full questionnaire lengths. Moreover, while these analyses did control for the effects of some other design characteristics of the included studies, more subtle aspects (such as the detail of instructions, which might be adapted to the protocol intensity in individual studies) were not included.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, meta-analyses on predictors of compliance have come to varying conclusions. While Morren and colleagues (2009) found that shorter questionnaires were associated with better compliance, two pooled data analyses (Rintala, Wampers, Myin-Germeys, & Viechtbauer, 2018;Soyster et al, 2019) and other metaanalyses have not detected an association between questionnaire length and compliance (Jones et al, 2018;Ono et al, 2019;Vachon et al, 2019). However, findings from these analyses have to be interpreted cautiously, since they faced limitations such as low variability in included questionnaire lengths (Rintala et al, 2018) and lack of sufficient information on questionnaire length or compliance in reviewed articles (Jones et al, 2018;Ono et al, 2019;Vachon et al, 2019).…”
Section: Sampling Frequencymentioning
confidence: 99%
“…Another limitation that should be mentioned is the relatively low compliance rate of 47.4% on the random EMA assessments. A recent meta-analysis showed that the average compliance rate for EMA studies in the substance use field is 75.1% (Jones et al, 2019). In the current study, we did not reimburse participants which may have led to lower compliance rate.…”
Section: Discussionmentioning
confidence: 75%
“…In the current study, we did not reimburse participants which may have led to lower compliance rate. The findings from the meta-analysis, however, suggest that possible moderators such as reimbursement and assessment burden, do not influence compliance rate (Jones et al, 2019). To reduce the risk of noncompliance due to competing priorities, participants were allowed up to 90 min to complete the random assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Test compliance, or lack thereof, seems to be problematic. A recent meta-analysis suggested that the compliance rate for EMA (the standard paradigm to administer mobile cognitive testing) with SUD samples was below the recommended rate of 80% (63). Designs including participant-initiated event-based assessments were associated with test compliance issues, whereas duration and frequency of assessment were not.…”
Section: Challenges For Implementation Into Practicementioning
confidence: 99%